Voor 1652 – Vakhistorici se interpretasies van die vroeë SuidAfrikaanse geskiedenis - Pieter de Klerk (Contree, 2012)
During the last few decades scholars from various disciplines, such as paleonthology, archeology, anthropology and linguistics, have steadily increased our knowledge of early South African history. Historians are dependent on the research of these scholars when writing interpretative overviews of South African history. In 1918 GM Theal included an account of South African history before 1652 in his multi-volume History of South Africa, but only since the 1970s have a number of professional historians studied the early phase of South African history. Richard Elphick made an important contribution to the study of the early Khoikhoi of the Western Cape. Other historians wrote overviews with a section on early history. Some of them regarded the early period primarily as an introduction to the history of South Africa since the seventeenth century, which, according to them, has the struggle between indigenous inhabitants and Western colonizers as its dominant theme. A few historians, such as HJ van Aswegen, wrote more extensively on early history, although Van Aswegen and his fellow-historians mainly provided a synthethis of research done by archeologists, anthropologists and linguists. Very little comparison with the history of other countries was done and very few problems regarding the research findings of scholars in the above-mentioned disciplines were pointed out. It is concluded that by paying more attention to the period before 1652 historians can provide new perspectives on major trends in the development of South African society.